2013
DOI: 10.1118/1.4826168
|View full text |Cite
|
Sign up to set email alerts
|

Separate modal analysis for tumor detection with a digital image elasto tomography (DIET) breast cancer screening system

Abstract: Digital Image Elasto Tomography (DIET) is a non-invasive breast cancer screening modality that induces mechanical vibrations into a breast and images its surface motion with digital cameras. A new approach in software based diagnosis of this surface motion is presented, focussing on the second natural frequency of the breast. Separate modal analysis is used to estimate the modal parameters using imaging data from silicone phantoms. The second natural frequency proves to be a reliable metric with the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Two sample t test was used to compare both groups, where null hypothesis was that both groups were from same distribution with unequal variance and equal means that shows area without inclusion. While if first group was different in normal distribution with lesser mean value shows region with inclusion [10].…”
Section: Applying Modal Analysismentioning
confidence: 90%
See 3 more Smart Citations
“…Two sample t test was used to compare both groups, where null hypothesis was that both groups were from same distribution with unequal variance and equal means that shows area without inclusion. While if first group was different in normal distribution with lesser mean value shows region with inclusion [10].…”
Section: Applying Modal Analysismentioning
confidence: 90%
“…Applying randomly fiducial markers left some of the unmarked regions which cause non-availability of motion data in that region. This creates blank or empty segments and effects accuracy of system [10]. This paper introduces Scale Invariant Feature Transform (SIFT) algorithm to extract keypoints on unmarked surface of breast.…”
Section: A the Diet Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Umut proposed a quantification method for percussion [16], vibrating the livers of animals with an impulse hammer to compare tissue properties according to their frequency responses. Kashif [17] analyzed the vibrated breast images to detect changes in stiffness. They reported that with respect to frequency, elastic moduli (storage elastic modulus, loss modulus) had different mechanical properties between normal and diseased tissues.…”
Section: Related Workmentioning
confidence: 99%